Productivity agreements and wage systems - North, D. T. B.; Buckingham, G. L. (London, Gower P., 1969)
This book is to provide a conceptual framework in which comprehensive productivity bargaining can be understood; to summarise the salient features of the experience gained so far, both from agreements which have been successful
Includes index
osa 23/01/19
Loans
Keywords: Wages and labour productivity